2014
DOI: 10.4236/as.2014.513139
|View full text |Cite
|
Sign up to set email alerts
|

Corn Yield Response to Reduced Water Use at Different Growth Stages

Abstract: To develop an efficient water use strategy for crop irrigation, we need to know how much water can be reduced without decreasing yield. A study was designed to determine corn growth stages at which water could be reduced without affecting grain yield, and at what soil moisture level water deficit stress begins in the plants in a silt loam soil. An experiment was conducted in a randomized complete block with a 3 × 4 factorial design in four replications, where treatments consisted of three soil moisture levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 23 publications
3
12
0
Order By: Relevance
“…Biophysical stress at different crop growth stages produces different magnitudes of influence on final yields [42,43]. Therefore, the relationship between NDVI residuals averaged over various growth stages and county level corn yields was investigated.…”
Section: Yield-ndvi Residual Relationshipmentioning
confidence: 99%
“…Biophysical stress at different crop growth stages produces different magnitudes of influence on final yields [42,43]. Therefore, the relationship between NDVI residuals averaged over various growth stages and county level corn yields was investigated.…”
Section: Yield-ndvi Residual Relationshipmentioning
confidence: 99%
“…Of these, maize has been adopted as one of the main succession crops to soya bean planting, playing an important role in grain production systems (Adegas, Voll, & Gazziero, ). However, factors such as lack of water, for example, have limited the productive potential of this crop (Kebede et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, factors such as lack of water, for example, have limited the productive potential of this crop (Kebede et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Under water stress, stomatal closure occurs to avoid water loss and prevent dehydration (Sperry, 2000) but stomatal and nonstomatal limitations are reported as the main causes of decreasing A under these conditions (Shangguan, Shao, & Dyckmans, 1999). In most drought‐tolerant species, stomata open quickly when water stress is relieved in order to maximize A , thus enhancing water productivity (WP; Atteya, 2003), which is an important parameter that quantifies the capacity of plants to use water efficiently (Kebede et al., 2014). Water productivity is defined by agronomists as the ratio of product (biomass or marketable yield) to the water needed to make that product (Sinclair, Tanner, & Bennett, 1984) or by plant physiologists as the ratio of carbon assimilated ( A ) to water used ( E ) to make that assimilate (Du, Kang, Zhang, & Davies, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown the effects of water stress on corn growth and physiology (Blum, 1996; Kebede et al., 2014; Subrahmanyam et al., 2006). However, little information is available on the physiological responses of silage corn to limited water, especially in semi‐arid conditions.…”
Section: Introductionmentioning
confidence: 99%